Development of self-righting hull from for unmanned surface vessel (USV) application [electronic resource] - 201809 Lee, Soo Chyi (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Teknologi Marin)) - Universiti Teknologi Malaysia, 2006